Extragastric Dieulafoy's lesion. (12th September 2014) - Gauci, James; Galea, Samuel; Galea, Joseph; Schembri, Mark
Abstract : A 74-year-old man on warfarin for aortic valve replacement presented with recurrent episodes of melaena. An initial oesophagogastroduodenoscopy (OGD) was normal, as were red cell scanning and colonoscopy. It was a third OGD that revealed the cause of the melaena—a vascular lesion in the duodenum, at the junction between D1 and D2. An extragastric Dieulafoy's lesion was diagnosed, and the lesion was injected with epinephrine and tattooed. Over the following months, episodes of bleeding recurred despite further attempts at injection. Percutaneous radiologically assisted embolisation of the gastroduodenal artery, and eventually duodenotomy and oversuturing of the lesion were performed to no avail. The patient has undergone over 10 endoscopies, and has received over 70 units of packed red cells to date, since his initial presentation 6 years ago. Attempts to stop the bleeding permanently have been difficult, highlighting the complexity of managing such a lesion.